Uncle Buck [videorecording (DVD)] - Candy, John; Madigan, Amy; Kelly, Jean Louisa; Hughes, John, 1950-2009 (Universal Home Video, 1998)
Uncle Buck, an idle good-natured bachelor, is left in charge of his nephew and nieces during a family crisis. While his carefree ways easily charm the younger relatives, he meets more than a little hostility from Tia, his rebellious teenage niece, and Chanice, his impatient girlfriend.